New Stable Cu(I) Catalyst Supported on Weakly Acidic Polyacrylate Resin for Green C-N Coupling: Synthesis of N-(Pyridin-4-yl)benzene Amines and N,N-Bis(pyridine-4-yl)benzene Amines - Kore, Nitin; Pazdera, Pavel (Molecules (Basel, Switzerland), 2016)
A method for preparation of a new stable Cu(I) catalyst supported on weakly acidic polyacrylate resin without additional stabilizing ligands is described. A simple and efficient methodology for Ullmann Cu(I) catalyzed C-N cross coupling reactions using this original catalyst is reported. Coupling reactions of 4-chloropyridinium chloride with anilines containing electron donating (EDG) or electron withdrawing (EWG) groups, naphthalen-2-amine and piperazine, respectively, are successfully demonstrated.
Keywords: Green Chemistry Technology; Catalysis; elektrony; Piperazine; Hydrogen-Ion Concentration; katalýza; piperaziny; recyclable green catalyst; Pyridinium Compounds; Aniline Compounds; pyridinové sloučeniny; Acrylic Resins; Electrons; supported Cu(I) catalyst; akrylové pryskyřice; měď; aniliny; Copper; 2-Naphthylamine; piperazin; opakované použití vybavení; polymer solid support; Piperazines; technologie zelené chemie; C-N coupling; 2-naftylamin; koncentrace vodíkových iontů; Equipment Reuse